2010
DOI: 10.1039/c0nr00574f
|View full text |Cite
|
Sign up to set email alerts
|

Imidazolium ionic liquids as promoters and stabilising agents for the preparation of metal(0) nanoparticles by reduction and decomposition of organometallic complexes

Abstract: The organometallic complexes ([Ru(COD)(2-methylallyl) 2 ] and [Ni(COD) 2 ] (COD ¼ 1,5-cyclooctadiene) dissolved in imidazolium ionic liquids (ILs) undergo reduction and decomposition, respectively, to afford stable ruthenium and nickel metal(0) nanoparticles (Ru(0)-NPs and Ni(0)-NPs) in the absence of classical reducing agents. Depending on the case, the reduction/auto-decomposition is promoted by either the cation and/or anion of the neat imidazolium ILs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
75
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 81 publications
(78 citation statements)
references
References 48 publications
3
75
0
Order By: Relevance
“…60 Furthermore, studies about the formation of ruthenium and nickel nanoparticles by decomposition of organometallic precursors in ionic liquids showed that (I) the anion plays an important role and (II) the IL itself is capable of inducing the decomposition by reaction with a complex. 9 In these cases minor amounts of IL suffered from decomposition and only traces of volatile compounds were detected in the gaseous phase, indicating decomposition of the IL.…”
Section: Synthesis Of Cu 2 O Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…60 Furthermore, studies about the formation of ruthenium and nickel nanoparticles by decomposition of organometallic precursors in ionic liquids showed that (I) the anion plays an important role and (II) the IL itself is capable of inducing the decomposition by reaction with a complex. 9 In these cases minor amounts of IL suffered from decomposition and only traces of volatile compounds were detected in the gaseous phase, indicating decomposition of the IL.…”
Section: Synthesis Of Cu 2 O Nanoparticlesmentioning
confidence: 99%
“…organo-boron, organo-tin, organo-zinc) reagents. 6 Nowadays metal nanoparticles, such as ruthenium, [7][8][9][10][11][12][13][14][15] platinum, 16 iridium, [17][18][19] palladium, 5,[20][21][22][23][24][25][26][27][28][29][30][31] cobalt, 32 and iron, 33 have great potential for application 34 in homogeneous and heterogeneous catalysis, including hydrogenation, 7 hydrogenolysis, 35 Fischer-Tropsch reactions 32,36 and cross-coupling reactions. 4,5,21,23 Copper 37 and especially copper(I)oxide 38 nanoparticles combine the high catalytic activity of precious metals with easy availability and low cost.…”
mentioning
confidence: 99%
“…[2][3][4][5] The development of new approaches for the synthesis and stabilisation of uniformly sized (or mono-dispersed) NPs constitutes a very important research area. [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] In this context, ionic liquids (ILs) have been proven to be suitable media for the generation and stabilisation of soluble metal NPs with small sizes, narrow size distribution and different shapes. 7,22 The IL forms a protective layer, which is probably composed of imidazolium aggregates located immediately adjacent to the nanoparticle surface, providing both steric and electronic protection against aggregation and/or agglomeration.…”
Section: Introductionmentioning
confidence: 99%
“…Surfactants, such as polymers/ dendrimers, [25][26][27][28] ligands and especially ionic liquids sufficiently shield the nanoparticles' surface and effectively prevent agglomeration. [12][13][14][15]19,29,30 Nanoparticles can be synthesised in various ways. There are several top-down and bottom-up methods with their inherent advantages and disadvantages.…”
Section: 24mentioning
confidence: 99%
“…Accordingly, ionic liquids are very popular concerning the synthesis of zero-and one-dimensional nanostructures. [4][5][6][7] Ionic liquids can act as solvents, cosolvents, [8][9][10][11] promoters, 12,13 reducing agents, [12][13][14][15] capping or protective agents and surfactants. 3,16 Despite their low melting points, ionic liquid phases show structural properties of lower order: they consist of polar and nonpolar nanoscale regimes which make them ideal templates for nanoscale synthesis.…”
Section: Introductionmentioning
confidence: 99%